Artificial Intelligence and Ethical Ijtihād in the Production of Islamic Knowledge - Eka Sutisna; Habibulloh Muqarrobin; Utami Rizkiyah; Hariyanto; Afriyani Mabruka Azzahro’ (Jurnal Lentera Insani, 2025)
Artificial Intelligence challenges the authority of ethical ijtihād in Islam by introducing machines as a new subject of knowledge production, forcing Islamic scholarly traditions to re-examine the boundaries between reason, values, and moral responsibility. The purpose of this study is to identify the epistemological and ethical challenges posed by artificial intelligence, formulate relevant principles of ethical ijtihād, and offer an implementation model for academics, scholars, and technology developers to use as a reference. This study uses a qualitative approach with a conceptual-analytical study design enriched by a critical literature review and reflective-normative analysis. The results confirm that artificial intelligence has transformed from a mere technical device into an epistemic infrastructure that actively influences the way Islamic knowledge is produced, distributed, and interpreted, especially in the context of pluralistic and digitised Muslim societies in Asia. The analysis shows that algorithms, large language models, and digital platforms open essential opportunities to expand access and strengthen religious literacy, but at the same time raise ethical issues such in algorithmic bias, epistemic injustice, the commercialisation of religion, and a shift in spiritual authority. These findings confirm that ethical ijtihād needs to be reconstructed as a reflective framework capable of responding to technological dynamics while remaining grounded in maqāṣid al-sharī‘ah, so that the relationship between humans, technology, and Islamic knowledge does not lose its orientation towards benefit and moral responsibility.